Evolution and Impact of Irrigation Laws and Policies in Nepal - Acharya, Janak Raj (Multi-Disciplinary Explorations: The Kasthamandap College Journal, 2024)
Nepal is mainly a mountainous country and has limited arable land. On the contrary, the annual water availability is much enough to provide year-round irrigation. Historically, Kathmandu valley was attributed for the network of irrigation systems supporting advanced and intensive agriculture activities in the past. At present, the federal structure allocates the responsibility of managing water resources to all three tiers of government on the basis of the size of projects. The National Irrigation Policy is to guide irrigation development in the country. It outlines governments plan for the irrigation sector and the strategies for attaining irrigation development objectives. Government of Nepal has made the Irrigation Rules, 2056 (2000) Irrigation (First Amendment) Rules, 2060 (2004). Irrigation policy, 2070 has envisaged providing sustainable and year-round irrigation service to all the agricultural land of the country to help increase agricultural productivity. The Government of Nepal has shared numerous treaties, negotiations and bilateral meeting minutes in the public domain. A number of bilateral, trilateral, and regional efforts are ongoing to foster cooperation and streamline concerted efforts. The bilateral cooperation mechanisms are through joint committees at various levels.